The needs of English for entrepreneurship students in the university level: The entrepreneurial role models’ prespective - Lailatul Rifah Rifah; Mardhatillah Shanti; Fardini Sabilah (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
The role of strategy was retained by universities to shape the quality of human resources to face the problems and challenges in the 21st century which linked to master both hard skills and soft skills. The main reason for analyzing the needs of entrepreneur from the role models to face industrial revolution era was the evolution of the need for college students graduate to be able to survive and compete with others. This research focused on the practitioner’s perspective on English mastery as one of the important parts of soft skills that should be mastered by the entrepreneurship students. Observation and in-depth-interview with five subject research used in this study in the qualitative method. Yin method used to analyze the data which included compiling, disassembling, reassembling, interpreting, and concluding the data until the saturation was achieved. This study reported that the ability to master English as a business language such as product description, presentation, negotiation, conversation, and emailing are very important to the entrepreneurship students. From studying the entrepreneurial role models, it is believed to represent sources of real inspiration and motivation to become successful entrepreneurs in the future.